Comparing The Effect Of Fes And Pnf Exercises To Help Stroke Patients Walk More Easily - Negi, Monika; S. Manivannan, S. Manivannan; G. Velmurugan, G. Velmurugan; Kamalam S, Gladies; Santheep S, Santheep S; R. Sindhuja, R. Sindhuja; Tharani, K.V. (Journal of Neonatal Surgery, 2025)
Background: Those who have had a stroke may find it difficult to walk, which makes getting about and being independent more challenging. This study investigated the effectiveness of Proprioceptive Neuromuscular Facilitation (PNF) and Functional Electrical Stimulation (FES) exercises in assisting stroke survivors with walking and performing other tasks. Methodology: 120 stroke patients with limited gait were part of a randomised controlled study. The groups for the participants were either the FES or the PNF ones. While FES targeted important muscle groups involved in gait, PNF focused on gait training, balance exercises, and muscular strengthening. Interventions ran for eight weeks, three times a week. Results: Gait qualities, muscular strength, balance, and functional mobility were assessed both before and after the intervention. Efficacy of PNF and FES statistically matched. Conclusion: This study guides doctors in selecting suitable therapies by comparing the efficacy of FES and PNF in improving gait and functional outcomes, thereby supporting stroke rehabilitation.